Wednesday

April 1, 2015

April 1, 2015

Posted by **angel** on Sunday, August 5, 2007 at 4:26pm.

Subtract 4x from both sides of the equation. Then divide both sides by -6. You should end up with an equation for y, as a function of x.

**Answer this Question**

**Related Questions**

math - Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T ...

Math - Emmy is 12. She writes an equation to find her mother's age, m. m - 12 + ...

Math - 4(j)-7=9 Add 7 to both sides of the equation and you get 4 j = 16 Now ...

maths - i have to make y the subject of this equation: 4t + 7y - 9 = 0 wod it be...

algebra - I need a step by step explanation on how to add these two equations 2x...

ALGEBRA - Select all the statements that can be used as steps to solve the ...

Algebra - Select all the statements that can be used as steps to solve the ...

math - 2x+4(1-x)=11+5x 2x+4-4x=11+5x 6x+4=11+5x 6x=7+5x x=7 i think this is it x...

Pre Cal - 6-x=2x+9 If you are to solve the equation for x, first try to get the ...

Algebra - I am re posting this for fear that it was overlooked earlier. I have ...